POSTPARTUM HAEMORRHAGE IN MATERNAL MOTHERS AT ANUTAPURA PUBLIC HOSPITAL IN PALU, 2017 - Nur, Rosmala; Sartika Sarina, Hasra; S Patui, Nurhaya; Radhiah, Sitti; Inriyanny Suwendro, Novi; Ariani,; A Pasinringi, Syahrir (International Journal of Psychosocial Rehabilitation, 2020)
Postpartum hemorrhage is one of the factors causing maternal mortality in Indonesia. In Indonesia, at least 128.000 women suffer from hemorrhage causing them to die. Data from the Anutapura Public Hospital in Palu showed that the rate of postpartum hemorrhage within 2015–2017 fluctuated and still caused maternal mortality. This study aimed to determine the risk factors of the incidence of postpartum hemorrhage in maternal mothers at Anutapura Public Hospital, Palu. The type of study was observational with a case-control approach. The subject of the study was mothers having a postpartum hemorrhage. The total sample of this study was 50 people as the case group and 100 people as the control group by adjusting the types of labor. Sampling was done using a total sampling technique. The data were analyzed using an odds ratio test with α = 5%. This study showed that anemia (OR=2.874 and CI=1.421-5.812), parity (OR=3.995 and CI=1.952-8.174), and age (OR=2.874 and CI=1.421-5.812) were the risk factors of postpartum hemorrhage in women. It can be concluded that anemia, parity, and age are the risk factors of postpartum hemorrhage in women. The importance of increasing ANC (antenatal care) visits is to control maternal and fetal health and provide information through a medical consultation about the importance of planning a good pregnancy.